A pricing strategy for demand-side regulation with direct load control: a nonconvex optimisation approach. (2017) - Ma, Kai; Wang, Congshan; Yang, Jie; Yuan, Chenliang; Guan, Xinping
This paper presents a pricing strategy to purchase the demand-side regulation service. Comparing with the traditional automatic generation control (AGC), the demand-side regulation service has lower cost and faster ramp rate, and thus can reduce the cost of the utility company. However, the payments for the demand-side regulation can also increase the cost. Thus, the cost of the utility company should be minimised by making a tradeoff between the demand-side regulation and the AGC. In this study, we formulate a cost minimisation problem considering the two-side regulation services. In general, the cost minimisation problem is nonconvex, and we use the forward method and golden section algorithm to obtain the globally optimal price for the demand-side regulation service. Numerical results demonstrate that the efficiency of the proposed model and the demand-side regulation can reduce the cost to the utility company significantly.